2022
DOI: 10.3390/ani12243548
|View full text |Cite
|
Sign up to set email alerts
|

Life History of the Arctic Squid Gonatus fabricii (Cephalopoda: Oegopsida) Reconstructed by Analysis of Individual Ontogenetic Stable Isotopic Trajectories

Abstract: Cephalopods are important in Arctic marine ecosystems as predators and prey, but knowledge of their life cycles is poor. Consequently, they are under-represented in the Arctic ecosystems assessment models. One important parameter is the change in ecological role (habitat and diet) associated with individual ontogenies. Here, the life history of Gonatus fabricii, the most abundant Arctic cephalopod, is reconstructed by the analysis of individual ontogenetic trajectories of stable isotopes (δ13C and δ15N) in arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 113 publications
0
1
0
Order By: Relevance
“…It may be that sperm whales adjust their foraging behavior to diel movements of potential prey species. For example, the Boreoatlantic armhook squid performs diurnal vertical migrations 69 . It has been shown that sperm whales adjust their foraging strategy to optimize the relationship between prey energetic value and the foraging energy cost at different depths or prey layers 48 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be that sperm whales adjust their foraging behavior to diel movements of potential prey species. For example, the Boreoatlantic armhook squid performs diurnal vertical migrations 69 . It has been shown that sperm whales adjust their foraging strategy to optimize the relationship between prey energetic value and the foraging energy cost at different depths or prey layers 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Main time series are ‘1900s’, ‘1930s’, ‘1970s’, ‘2000s’ and ‘2010s’, while ‘late XIX th century’ with n = 2 were only used in some analyses (see below). Stable isotope data on ‘contemporary’ G. fabricii beaks, sampled in 2016, 2017 and 2019 in the Baffin Bay and Davis Strait were previously analysed in Ref [ 54 ]. We did not pool these beaks with the ‘2010s’ from this study (sampled in 2014) because the ‘2010s’ were from the Nordic Seas and δ 13 C values in G. fabricii were significantly different between the Nordic Seas and Baffin Bay [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cephalopods have chitinous jaws (= beak) to cut their prey into smaller pieces [ 50 , 51 ]. The beaks were successfully used as archival tissue for detailed SIA life history reconstructions of contemporary cephalopods in the Arctic and Antarctic [ 52 54 ]. However, there is only a single study from the Atlantic that involves historical squid, where the sample size ( n = 4) is too small to assess potential ecosystem implications [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oegopsid data must be pieced together from a variety of indirect methods, including stable isotopes and other elemental analyses of beaks and gladii. These methods have been essential in understanding how deep-sea species occupy different water masses or localities their life cycles (e.g., Cherel and Hobson, 2005;Semmens et al, 2007;Zumholz et al, 2007;Lukeneder et al, 2008;Staudinger et al, 2013;Golikov et al, 2018;Golikov et al, 2022b).…”
Section: Patterns Of Cephalopod Life Cyclesmentioning
confidence: 99%